Contrasting life‐history strategies of three sympatric icefish species in the northern Scotia Sea - Huw W. James; Timothy Jones; Fabrice Stephenson; Philip R. Hollyman; William D. K. Reid; Martin A. Collins (Journal of Fish Biology, 2026)
Comprehending a species' life‐history strategies is crucial to inform effective conservation efforts. Commercial fishing impacts icefish (family: Channichthyidae) in the Scotia Sea, but detailed information on species‐specific life histories remains largely unknown. In this study, the demographic characteristics of mackerel icefish ( Champsocephalus gunnari ), blackfin icefish ( Chaenocephalus aceratus ) and South Georgia icefish ( Pseudochaenichthys georgianus ) were examined and used to compare inferred life‐history strategies, using long‐term data from demersal and plankton trawl surveys conducted across the South Georgia and the Shag Rocks continental shelves. The results indicated that C. gunnari may exhibit alternative reproductive tactics, as they appear to spawn multiple times in a single year and mature at varying sizes. Conversely, C. aceratus and P. georgianus reproduced once per annum and appeared to favour investing in somatic growth, resulting in them consistently maturing at a larger size. Seasonal sex ratios demonstrated a reduction in captured mature males for C. aceratus and P. georgianus during the suspected spawning period, supporting the hypothesis of sex‐specific behavioural patterns during the reproductive period. These findings highlight the variation in the life‐history strategies among these three icefish species, which should be considered during the development of future management measures.